Performance analysis of high-k materials as stern layer in ion-sensitive field effect transistor using commercial TCAD - Ahmed M. Dinar; AS Mohd Zain; F. Salehuddin; Mowafak K. Mohsen; Mothana L. Attiah; M. K. Abdulhameed (Universitas Ahmad Dahlan, 2019)
High-k materials as a STERN Layer for Ion-Sensitive-Field-Effect-Transistor (ISFET) have improved ISFET sensitivity and stability. These materials decrease leakage current and increase capacitance of the ISFET gate toward highest current sensitivity. So far, many high-k materials have been utilized for ISFET, yet they were examined individually, or using numerical solutions rather than using integrated TCAD environment. Exploiting TCAD environment leads to extract ISFET equivalent circuit parameters and performs full analysis for both device and circuit. In this study we introduce a comprehensive investigation of different high-k material, Tio2, Ta2O5, ZrO2, Al2O3, HfO2 and Si3N4 as well as normal silicon dioxide and their effects on ISFET sensitivity and stability. This was implemented by developing commercial Silvaco TCAD rather than expensive real fabrication. The results confirm that employing high-k materials in ISFET outperform normal silicon dioxide in terms of sensitivity and stability. Further analysis revealed that Titanium dioxide showed the highest sensitivity followed by two groups HfO2, Ta2O5 and ZrO2, Al2O3 respectively. Another notable exception of Si3N4 that is less than other materials, but still have higher sensitivity than normal silicon dioxide. We believe that this study opens new directions for further analysis and optimization prior to the real cost-ineffective fabrication.